Evaluation of public policies in Spain: Análisis de dos décadas de representación mediática - Castelló-Sirvent, Fernando; Peris-Ortiz, Marta (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This article studies the evolution of the media representation of the evaluation of public policies in Spain during the last two decades. 11.107 news items published in 260 Spanish press media are analyzed and the intertemporal evolution of the discourse configured by the media in public opinion is evaluated. A relevant finding of the research involves verifying the transversality of the topics discussed, the dispersion and its link with institutions that promote the debate in each sector. Among the main thematic nuclei, the link with the Sustainable Development Goals (SDG) and the decisive impulse carried out by the universities stand out.